The Formation of the Jiaodong Gold Province. (30th December 2022) - DENG, Jun; WANG, Qingfei; LIU, Xuefei; ZHANG, Liang; YANG, Liqiang; YANG, Lin; QIU, Kunfeng; GUO, Linnan; LIANG, Yayun; MA, Yao
Abstract : Abstract: Gold deposits in Jiaodong, termed Jiaodong‐type, are tectonically located in the southeastern margin of the North China Craton. Their major features are reviewed in this paper to highlight the differences between Jiaodong deposits and other genetic types of gold deposits. The mineralization was synchronized with asthenosphere upwelling indicated by syn‐ore OIB‐like mafic dike and large‐scale crustal thinning suggested by decrease of Sr/Y from pre‐ore to syn‐ore granites. Asthenosphere upwelling induced by the roll‐back of Paleo‐Pacific Plate drove partial melting of lithospheric mantle and devolatilization, which induced the release of the ore‐forming fluids. In concomitant with magmatic records, mineralization migrated from the western Jiaobei terrane (133–127 Ma) to the eastern Sulu orogenic belt (114–108 Ma), corresponding to the eastward roll‐back of Paleo‐Pacific Plate. Gold mineralization in Jiaodong formed in the transitions of ductile to brittle deformation, rapid to slow crustal uplift, and regional compression to extension. In the regional‐scale, the gold deposits in the Jiaobei terrane are mostly situated at intersections between NE‐trending faults and EW‐trending basement faults, and gold orebodies dominantly controlled by the lithologic contacts between Precambrian metamorphic rocks and Mesozoic granites. The mineralization was dominated by the disseminated‐veinlet ores related to quartz–sericite alteration in strong cataclasite‐breccia zone, with subsidiary thick quartz‐sulfide veins developed in secondary fault zones. The ore‐forming fluids belong to a H2 O–CO2 –NaCl±CH4 system and show minor variations in salinity among different types of ore. Structure‐fluid feedback involving fluid‐rock reaction and hydrofracturing triggered the fluid phase separation and resultant gold deposition. The Jiaodong gold deposits are distinct from orogenic and intrusion‐related gold deposits in terms of tectonic setting, origin of ore‐forming fluids, and mechanism of gold deposition.